Kondisi sosial ekonomi pelaku usaha pengolahan ikan Baby Tuna (Thunnus obesus) dan Cakalang (Katsuwonus pelamis) yang di pasarkan di Kota Kendari - Rahmasari, Wa Ode Fahniyola; Riani, Irdam; Huli, La Ode; Patiung, Seventry Meliana (Universitas Halu Oleo, 2024)
This study aims to determine the socio-economic conditions of business actors processing baby tuna (Thunnus obesus) and skipjack tuna (Katsuwonus pelamis) which marketed in Kendari City. This research was carried out on October 2021 in Kendari City. The population in this study were 32 of fish processing businessmen. The sampling technique used was purposive sampling taking into account the criteria for fish processing of baby tuna (T. obesus) and skipjack (K. pelamis) as many as 11 respondents. The data observed included age, education level, business experience, number of family dependents, housing conditions, means of transportation, income, expenses and sources of capital. Data collection techniques were interviews, observation, literature study, and documentation. Data analysis was carried out in a qualitative descriptive. The results showed that social conditions of businessmen of fish processing of average of age and school alumni were 43.5 years and high school education. They have experience time in this businessfor average 15 years. The number of their family dependents were 4 people. While the average economic condition of the businessman showed that they have had own house with roof of the zinc type. The house type of fish businessman consisted of permanent, semi-permanent and non-permanent walls, and the house floor had cement or ceramic floors. Their transportation of the businessmen have a motorbike. Their average income were IDR 5,000,000. Their average of food expenditure and non-food expenditure were IDR 412,727 and IDR 1,148,909, respectively. While the source of capital was more dominant using their own capital. The conclusion of this study was that in terms of social criteria, the fish businessmen in this village were productive age, highly educated, experienced in the baby tuna business, high number of dependents. Meanwhile, from the aspect of economic condition, the fish businessmen had high-income economic criteria, and the amount of non-food expenditure of the businessmen have more higher than their food expenditure.